Comparing the effects of highly aspherical lenslets versus defocus incorporated multiple segment spectacle lenses on myopia control - Hui Guo; Xianfang Li; Xiaoxiao Zhang; Haizhao Wang; Jianhua Li (Scientific Reports, 2023)
Abstract To compare spectacle lenses with highly aspherical lenslets (HAL) versus defocus incorporated multiple segments (DIMS) on myopia progression control in 1 year. This retrospective cohort study involved data from children prescribed HAL or DIMS spectacle lenses in Guangzhou Aier Eye Hospital, China. To address the discrepancy that some children followed up at less than or more than 1 year, the standardized 1-year spherical equivalent refraction (SER) and axial length (AL) changes from baseline were calculated. The mean differences in the changes between the two groups were compared with linear multivariate regression models. Age, sex, baseline SER/AL, and treatment were included in the models. A total of 257 children who qualified for the inclusion criteria were included for the analyses (193 in the HAL group and 64 in the DIMS group). After controlling baseline variates, the adjusted mean (standard error, SE) of the standardized 1-year changes in SER for HAL and DIMS spectacle lens users were − 0.34 (0.04) D and − 0.63 (0.07) D, respectively. HAL spectacle lenses reduced myopia progression by 0.29 D (95% confidence interval [CI] 0.13 to 0.44 D) at 1 year compared to DIMS lenses. Accordingly, the adjusted mean (SE) ALs increased by 0.17 (0.02) and 0.28 (0.04) mm for children wearing HAL lenses and DIMS lenses, respectively. HAL users had 0.11 mm less AL elongation (95% CI − 0.20 to − 0.02 mm) than DIMS users. Age at baseline was significantly associated with AL elongation. Chinese children wearing spectacle lenses designed with HAL had less myopia progression and axial elongation than those wearing spectacle lenses designed with DIMS.